2019
DOI: 10.1186/s12881-019-0833-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of HLA-DRB1 alleles in Mexican mestizo patients with abdominal aortic aneurysms

Abstract: Background Multiple factors are implicated in the etiology and pathogenesis of Abdominal Aortic Aneurysms (AAA). Available literature of genetic studies has previously suggested the possible roles of autoimmunity, genetic predisposition and ethnic susceptibility. Due to the association with autoimmune diseases and proven application in population genetics, we aimed to investigate alleles of the Class II Human Leukocyte Antigens (HLA-DRB1) in the Mexican Mestizo population with aortic aneurysms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…The differences observed between small and large AAA only for the V segment genes suggest that the two subgroups of AAA patients may trigger a different T-cell immune response, which would depend on specific interactions of the TCR with certain HLA molecules expressed by APCs. This observation is supported by various studies showing significant associations between AAA and the expression of both specific class I and II HLA alleles, although these findings are controversial (Tilson et al, 1996;Tromp et al, 2006;Badger et al, 2007;Anaya-Ayala et al, 2019). There are several possible explanations for these inconclusive results: for instance, the immune response restricted to specific HLA molecules is not constant throughout the course of the disease, but may change and differentially characterize the early and late stages of disease progression, as we inferred by highlighting the observed differences between patients with small and large AAA.…”
Section: Discussionmentioning
confidence: 59%
“…The differences observed between small and large AAA only for the V segment genes suggest that the two subgroups of AAA patients may trigger a different T-cell immune response, which would depend on specific interactions of the TCR with certain HLA molecules expressed by APCs. This observation is supported by various studies showing significant associations between AAA and the expression of both specific class I and II HLA alleles, although these findings are controversial (Tilson et al, 1996;Tromp et al, 2006;Badger et al, 2007;Anaya-Ayala et al, 2019). There are several possible explanations for these inconclusive results: for instance, the immune response restricted to specific HLA molecules is not constant throughout the course of the disease, but may change and differentially characterize the early and late stages of disease progression, as we inferred by highlighting the observed differences between patients with small and large AAA.…”
Section: Discussionmentioning
confidence: 59%
“…2) In the case of abdominal aortic aneurysms, lesions that can occur secondary to TA, recently, we reported increased frequen-cies of the alleles HLA-DRB1*01 and HLA-DRB1*16 in Mexican Mestizo patients with degenerative aneurysms and associations with MHC genes, suggesting a possible relationship with this vasculitis. 10) As regards non-MHC genes, authors, including Terao, 2) have found and reported evidence of associations with TA as the one located in the IL12B region. In the twin sisters presented in this article, we did not investigate non-MHC haplotypes, but this is an area that deserves further research to increase our understanding of the pathogenesis of TA and identify those individuals genetically susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…The presented result of the association of the HLA-A-Bw4 molecule with aneurysm size seems to be related to local inflammation and autoimmunity in the affected aorta. The HLA system is currently being studied in terms of autoimmunity in AAA patients, but the research is mainly focused on understanding the expression of HLA class II in this group of patients [ 35 , 36 ]. However, the data so far are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…There are documented links of the allele HLA-DQA1*0102 with the occurrence of AAA [ 35 ]. In addition, HLA-DRB1*01 and HLA-DRB1*16 have been suggested to be involved [ 36 ]. However, little is known about the role of HLA class I molecules in the formation and development of AAA.…”
Section: Discussionmentioning
confidence: 99%